Writing Results Section of a Scientific Article (Advancements in Homeopathic Research, 2023)
Research is the foundation of an evidence-based  practice. The Results section of a research paper  presents novel outcomes of the research work. It  involves systematically presenting and describing  the outcomes of the study. In this article, practical  aspects of writing the results of a scientific research  article are discussed.
Keywords: Evidence-based practice; Results section; Research outcomes; Scientific article